Adipose tissue oxygenation is associated with insulin sensitivity independently of adiposity in obese men and women. Issue 9 (9th May 2018) - Goossens, Gijs H.; Vogel, Max A. A.; Vink, Roel G.; Mariman, Edwin C.; van Baak, Marleen A.; Blaak, Ellen E.
Abstract : Adipose tissue (AT) dysfunction contributes to the pathophysiology of insulin resistance and type 2 diabetes. Previous studies have shown that altered AT oxygenation affects adipocyte functionality, but it remains to be elucidated whether altered AT oxygenation is more strongly related to obesity or insulin sensitivity. In the present study, we tested the hypothesis that AT oxygenation is associated with insulin sensitivity rather than adiposity in humans. Thirty‐five lean and obese individuals (21 men and 14 women, aged 40‐65 years) with either normal or impaired glucose metabolism participated in a cross‐sectional single‐centre study. We measured abdominal subcutaneous AT oxygenation, body composition and insulin sensitivity. AT oxygenation was higher in obese insulin resistant as compared to obese insulin sensitive (IS) individuals with similar age, body mass index and body fat percentage, both in men and women. No significant differences in AT oxygenation were found between obese IS and lean IS men. Moreover, AT oxygenation was positively associated with insulin resistance ( r = 0.465; P = .005), even after adjustment for age, sex and body fat percentage (standardized β = 0.479; P = .005). In conclusion, abdominal subcutaneous AT oxygenation is associated with insulin sensitivity both in men and women, independently of adiposity. AT oxygenation may therefore be a promising target to improve insulin sensitivity.